CRIP1a inhibits endocytosis of G-protein coupled receptors activated by endocannabinoids and glutamate by a common molecular mechanism - Mascia, Fabrizio; Klotz, Lisa; Lerch, Judith; Ahmed, Mostafa H.; Zhang, Yan; Enz, Ralf (Journal of Neurochemistry, 2017)
The excitability of the central nervous system depends largely on the surface density of neurotransmitter receptors. The endocannabinoid receptor 1 (CB1 R) and the metabotropic glutamate receptor mGlu8 R are expressed pre-synaptically where they reduce glutamate release into the synaptic cleft. Recently, the CB1 R interacting protein cannabinoid receptor interacting protein 1a (CRIP1a) was identified and characterized to regulate CB1 R activity in neurons. However, underlying molecular mechanisms are largely unknown. Here, we identified a common mechanism used by CRIP1a to regulate the cell surface density of two different types of G-protein coupled receptors, CB1 R and mGlu8a R. Five amino acids within the CB1 R C-terminus were required and sufficient to reduce constitutive CB1 R endocytosis by about 72% in the presence of CRIP1a. Interestingly, a similar sequence is present in mGlu8a R and consistently, endocytosis of mGlu8a R depended on CRIP1a, as well. Docking analysis and molecular dynamics simulations identified a conserved serine in CB1 R (S468) and mGlu8a R (S894) that forms a hydrogen bond with the peptide backbone of CRIP1a at position R82. In contrast to mGlu8a R, the closely related mGlu8b R splice-variant carries a lysine (K894) at this position, and indeed, mGlu8b R endocytosis was not affected by CRIP1a. Chimeric constructs between CB1 R, mGlu8a R, and mGlu8b R underline the role of the identified five CRIP1a sensitive amino acids. In summary, we suggest that CRIP1a negatively regulates endocytosis of two different G-protein coupled receptor types, CB1 R and mGlu8a R.
EVALuna2:4771